Antiseizure medication nonadherence and its associated factors among Epileptic patients in Ethiopia, a systematic review and meta-analysis. (October 2021) - Amha, Haile; Memiah, Peter; Getnet, Asmamaw; Mengist, Belayneh; Gedfew, Mihretie; Ayenew, Temesgen; Akalu, Tadesse Yirga; Mulugeta, Henok; Bewket, Bekalu; Kebede, Bekalu; Petrucka, Pammla
Highlights: This systematic review and meta-analysis reported the magnitude of anti-seizure medication non adherence and associated factors among patients with epilepsy in Ethiopia. This review reported that more than two-fifth of patients with epilepsy had anti-epileptic drug non adherences in Ethiopia. Policy makers need to give attention and develop strategies to increase the level of medication adherence among epileptic patients. Abstract: Background: The majority of patients with epilepsy in resource-poor countries never receive proper treatment, and those who are started on anti-seizure medications quickly discontinue them. Medication noncompliance is extremely common, with estimates ranging from 26 to 79 percent. Non-adherence to antiseizure medications is associated with poor seizure control, increased morbidity, increased hospitalization time, poor quality of life, increased health care costs, and increased mortality in adults. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2009 guideline was used for this systematic review and meta-analysis. The databases Pub Med, Cochrane Library, Scopus Online, and Google Scholar were all searched. STATA™ version 11 software was used for the meta-analysis. The I 2 test and Egger's tests were used to assess heterogeneity and publication bias. The random-effects method was used to estimate the pooled adherence level with a 95 percent confidence interval. Results: This meta-analysis included twelve Ethiopian studies involving a total of 3416 epileptic patients. The national pooled prevalence of antiseizure medication non-adherence was 41.96%. Patients who paid for their medications, took them for more than a year, had co-morbidity, and felt stigmatized were more likely to be non-adherent than their counterparts. Conclusion: According to this systematic review and meta-analysis, more than two out of every five epileptic patients did not take their antiseizure medications as prescribed. Clinicians must educate epileptic patients about the importance of medication adherence. Systematic review registration: The review has been registered on an International Prospective Register of Systematic Review with registration number CRD42019142905.